Self-assembling peptides as immunomodulatory biomaterials - Hernandez, Andrea; Hartgerink, Jeffrey D.; Young, Simon (Frontiers in Bioengineering and Biotechnology, 2023)
Self-assembling peptides are a type of biomaterial rapidly emerging in the fields of biomedicine and material sciences due to their promise in biocompatibility and effectiveness at controlled release. These self-assembling peptides can form diverse nanostructures in response to molecular interactions, making them versatile materials. Once assembled, the peptides can mimic biological functions and provide a combinatorial delivery of therapeutics such as cytokines and drugs. These self-assembling peptides are showing success in biomedical settings yet face unique challenges that must be addressed to be widely applied in the clinic. Herein, we describe self-assembling peptides’ characteristics and current applications in immunomodulatory therapeutics.